Control interno y su incidencia en los productos financieros de la cooperativa de ahorro y crédito Sumak kawsay del cantón la mana año 2019 – 2020 - Tigre Mendoza, Jimena Lisseth (2021)
The Internal Control in the financial products offered by the Sumak Kawsay Ltda. Agency La Mana Savings and Credit cooperative, presents weakness in compliance with the Policies and Regulations in the entity, likewise the Cooperative has well-directed financial indicators, therefore The administration of the loan portfolio managed by the La Maná agency has a delinquency percentage within the allowed standards, therefore the risk level increases by 2020 with (0.15%). The main objective of this project focuses on compliance with Internal Control in Financial Products and a reduction in the level of risk that affects the credit administration of the cooperative and its management, in addition to serving as a tool for its managers in making decision-making, increasing control and monitoring of credit processes that are handled internally. The qualitative-quantitative methodology will allow to address the problematic dealt with the topic to be investigated for it requires applying inductive, deductive, exploratory, historical-logical methods, in order to evaluate and interpret the data obtained through direct observation, interview and relevant documentation for evidence the procedures. As results, it is intended to describe the shortcomings, problems and inconveniences raised within the processes and activities in financial products, they will be made known to the pertinent authorities so that the preventive and corrective measures they deem appropriate are taken. Keywords: internal control - financial products, Investment attraction, credit placement.